Gypsum-Based Material for Dental Pulp Capping: Effect of Chitosan and BMP-2 on Physical, Mechanical, and Cellular Properties. (26th July 2018) - Subhi, Hasan; Reza, Fazal; Husein, Adam; Al Shehadat, Saaid Ayesh; Nurul, Asma-Abdullah
Abstract : Effective pulp capping material must be biocompatible and have the ability to induce dentin bridge formation as well as having suitable physical and mechanical properties; however, many current materials do not satisfy the clinical requirements. This study aimed to assess the physical and mechanical properties of gypsum-based chitosan material (Gp-CT) and to evaluate its effects on cellular properties of stem cells from human exfoliated deciduous teeth (SHED). The experimental material was prepared with different concentrations of chitosan (CT) with or without BMP-2. Then, setting time, compressive strength, and pH were determined. In addition, cell viability, alkaline phosphatase (ALP) activity, and cell attachment were assessed. The setting time, compressive strength, and pH obtained were 4.1–6.6 min, 2.63–5.83 MPa, and 6.5–5.7, respectively. The cell viability to gypsum (Gp) with different CT concentrations was similar to that of the control on day 1 but statistically different from that of Gp alone on day 3. The ALP activity of SHED was significantly higher (p < 0.05) in CT- and BMP-2-containing materials than those in the control and Dycal at days 3 and 14. The scanning electron microscopy (SEM) image revealed that flattened cells were distributed across and adhered to the material surface. In conclusion, Gp-CT material shows promise as a potential material for direct pulp capping.